Multicontrast MR Imaging at 7T in Multiple Sclerosis: Highest Lesion Detection in Cortical Gray Matter with 3D-FLAIR - Kilsdonk, I.D.; de Graaf, W.L.; Soriano, A. Lopez; Zwanenburg, J.J.; Visser, F.; Kuijer, J.P.A.; Geurts, J.J.G.; Pouwels, P.J.W.; Polman, C.H.; Castelijns, J.A.; Luijten, P.R.; Barkhof, F.; et al. (American Journal of Neuroradiology, 2013)
BACKGROUND AND PURPOSE: 7T MR imaging has led to improved detection and classification of cortical MS lesions, mainly based on T2*-weighted gradient-echo sequences. Depiction of cortical GM by using the recommended MS imaging protocol has not yet been investigated at 7T. We aimed to investigate prospectively which recommended sequence for clinical use has the highest value at 7T, in terms of GM and WM lesion detection. MATERIALS AND METHODS: Thirty-seven patients with MS (mean age, 43.8 years; 25 women) and 7 healthy controls (mean age, 40.4 years; 5 women) underwent multicontrast 7T MR imaging including the recommended clinical 2D-T2WI, 3D-T1WI, 3D-FLAIR, and GM-specific 3D-DIR. Lesions were scored and categorized anatomically by 3 raters, in consensus. The value of sequences was evaluated lesion-wise and patient-wise (Wilcoxon signed-rank test). RESULTS: At 7T, 3D-FLAIR detected the highest number of total cortical GM lesions (217), 89% more than 3D-DIR and 87% and 224% more than 2D-T2WI and 3D-T1WI. Patient-wise analysis showed that this difference between 3D-FLAIR and 3D-DIR was statistically significant (P < .04), and most pronounced for the number of mixed lesions (P < .03). 3D-FLAIR also detected the highest number of total WM lesions (2605), but the difference with 3D-DIR and 3D-T1WI was not significant. CONCLUSIONS: When using recommended clinical sequences at 7T, the best way to detect cortical GM lesions is with 3D-FLAIR and not by GM-specific 3D-DIR or by conventional 2D-T2WI and 3D-T1WI sequences. 2D-T2WI2D dual-echo T2-weightedDIRdouble inversion recoveryGMgray matterMAGNIMSMagnetic Imaging in MSmixedmixed GM/WM matter